Peranan Guru dalam Meningkatkan Kualitas Pembelajaran Sejarah bagi Generasi Z - Kamelia Putri; Osep Ismana; Tubagus Umar Syarif Hadi Wibowo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Currently is the era of generation Z where this generation is a generation that is interconnected with cyberspace. However, this results in learning in the classroom being adjusted to innovative ways in applying learning concepts to make it fun. History educators or teachers must understand the characteristics of generation Z because the majority of students they face in the classroom are part of generation Z. History educators must innovate to utilize existing gadgets or technology in history learning, so that history learning becomes contextual and fun. The use of the right media and methods in learning history will be able to increase the explosiveness of creativity, innovation, critical thinking, and productivity skills of students in learning history at school, especially in the classroom.